Transcriptional and Translational Relationship in Environmental Stress: RNAseq and ITRAQ Proteomic Analysis Between Sexually Reproducing and Parthenogenetic Females in Moina micrura - Jia, Jingyi; Liu, Xiangjiang; Li, Lu; Lei, Chengqiang; Dong, Ying; Wu, Guoqiang; Hu, Guangfu (Frontiers in Physiology, 2018)
Moina micrura is a kind of small-bodied water flea within the family Moinidae. Similar to Daphnia, M. micrura could also switch its reproduction mode from parthenogenetic female (PF) to sexual female (SF) to adapt to the external environment. To uncover the mechanisms of reproductive switching in M. micrura, we used both RNA-Seq and iTRAQ analyses to investigate the differentially expressed genes (DEGs) and their protein products between SF and PF in M. micrura. A total of 1665 DEGs (702 up-regulated, 963 down-regulated) and 600 differentially expressed proteins (DEPs) (102 up-regulated, 498 down-regulated) were detected in SF. Correlation analyses indicated that 31 genes were expressed significantly differentially at both transcriptomic and proteomic levels, including 15 up-regulated genes and 16 down-regulated genes in SF. Meanwhile, our data also showed that 528 DEPs have discordant expression at transcript level, implying post-transcriptional (including translational) regulation. These top up-regulated genes and their protein products in SF were mainly grouped into the globin-related family, vitellogenin-related family, cuticle-related family, Hsp-related family and methyltransferases-related family, which were all involved in the reproductive switching in Daphnia. In contrast, a cluster of orthologous groups revealed that up-regulated genes and their protein products in PF were strongly associated with the metabolic process, which may be responsible for rapid population proliferation in M. micrura.